Clean One-Pot Multicomponent Synthesis of Pyrans Using a Green and Magnetically Recyclable Heterogeneous Nanocatalyst - Ghassemi, Mina; Maleki, Ali (SynOpen, 2021)
Copper ferrite (CuFe2O4) magnetic nanoparticles (MNPs) were synthesized via thermal decomposition and applied as a reusable and green catalyst in the synthesis of functionalized 4H-pyran derivatives using malononitrile, an aromatic aldehyde, and a β-ketoester in ethanol at room temperature. The nanoparticles were characterized by FT-IR, EDX, SEM, TGA, and DTG analysis. The catalyst was recovered from the reaction mixture by applying an external magnet and decanting the mixture. Recycled catalyst was reused for several times without significant loss in its activity. Running the one-pot three-component reaction at room temperature, using a green solvent under environmentally friendly reaction conditions, ease of catalyst recovery and recyclability, no need for column chromatography and good to excellent yields are advantages of this protocol.
Keywords: green chemistry; multicomponent reactions; magnetic nanoparticles; pyran